2006
DOI: 10.1093/humrep/del425
|View full text |Cite
|
Sign up to set email alerts
|

Increased telomerase activity and human telomerase reverse transcriptase mRNA expression in the endometrium of patients with endometriosis

Abstract: This study showed the overexpression of hTERT mRNA and telomerase activity in the endometrium of endometriosis patients. These finding suggest that replication potential of endometrial cells may have an important role in the pathogenesis of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 27 publications
4
35
0
Order By: Relevance
“…Several studies have demonstrated that both telomerase activity and expression are significantly upregulated in the endometrium with endometriosis, which also shows subfertility and low implantation rate (Kim et al, 2007;Hapangama et al, 2008b;Mafra et al, 2014). Considering our data, we concluded that telomerase may contribute to a dysfunctional endometrium during the implantation window in RIF patients.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Several studies have demonstrated that both telomerase activity and expression are significantly upregulated in the endometrium with endometriosis, which also shows subfertility and low implantation rate (Kim et al, 2007;Hapangama et al, 2008b;Mafra et al, 2014). Considering our data, we concluded that telomerase may contribute to a dysfunctional endometrium during the implantation window in RIF patients.…”
Section: Discussionsupporting
confidence: 59%
“…Telomerase has been well studied in the context of cell oncogenesis, senescence, and immortalization (Stewart et al, 2012;Ye et al, 2014). Recently, several studies have also revealed that telomerase is closely involved in female reproductive health (Kim et al, 2007;Hapangama et al, 2008a;Hapangama et al, 2008b;Chen et al, 2011;Mafra et al, 2014). In the human endometrium, the mRNA of telomerase reverse transcriptase (Tert), which encodes the catalytic subunit of telomerase, is highly expressed in epithelial cells (Tanaka et al, 1998;Hapangama et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Irregular function of these SCs may contribute to the pathogenesis of endometriosis and the growth of tissue outside the uterine cavity, causing dysmenorrhoea, subfertility and endometrial carcinoma [30]. Stem cells that are ectopically distributed through lymphovascular metastasis [31] may also contribute to the pathogenetic process, because their high proliferation promotes rapid clonal expansion [32]. …”
Section: Introductionmentioning
confidence: 99%
“…The abnormal existence or hyperplasia of cells is thought to be associated with the pathogenesis of a number of diseases (8). Numerous putative stem cell markers have been previously described (9,10). Differentiated cells are produced by the ectopic expression of specific transcription factors, including SRY-box containing gene 2 (SOX2), octamer-binding transcription factor 4 (Oct-4), KrĆ¼eppel-like factor 4 (KLF-4), homeobox protein NANOG (NANOG), C-X-C chemokine receptor type 4 (CXCR4) and cellular homolog of the oncogenic retrovirus v-myc oncogene (c-Myc), and subsequently form pluripotent stem cells (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%